Membangun Loyalitas Wisatawan Melalui Peningkatan Kualitas Objek Wisata dan Promosi Wisata pada Wisata Kampung Pecinan Surabaya - Salma Dea Nabilla; Muhammad Irham Adhitya; Ferdy Setiyawan; Raden Johnny Hadi Raharjo; Nanik Hariyana (Cv. Utility Project Solution, 2022)
Tight competition in the tourism industry forces tourism managers to find innovations to gain customer loyalty to compete with other tourism competitors. The Chinatown Village Tourism Surabaya strives to build tourist loyalty through improving the quality of tourist objects and tourism promotion. The approach used in this community service activity is a cognitive loyalty approach that makes information the primary source of achieving tourist loyalty. Based on the results of community service at the Chinatown Village Tourism in Surabaya, the efforts made to improve the quality of tourist objects are by making tourist maps, murals, and SOP. The efforts made in increasing promotion are by creating a website and implementing Integrated Marketing Communication.